2018
DOI: 10.3897/zookeys.801.29580
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial isopods in urban environments: an overview

Abstract: In an increasingly urbanized world scientific research has shifted towards the understanding of cities as unique ecosystems. Urban land use change results in rapid and drastic changes in physical and biological properties, including that of biodiversity and community composition. Soil biodiversity research often lags behind the more charismatic groups such as vertebrates and plants. This paper attempts to fill this gap and provides an overview on urban isopod research. First, a brief overview on urban land use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 107 publications
0
11
0
1
Order By: Relevance
“…Urbanization could be harmful to organism as it induced direct habit loss, soil pollution, and strong disturbance (McKinney, 2006;Knop, 2016;Sanchez-Bayo and Wyckhuys, 2019). In contrast, urban habitats provide many resources for soil fauna, such as water from irrigation, food from garbage, and refuge sites in gardens and under paving stones (Jones and Leather, 2012;Hornung et al, 2018;Szlavecz et al, 2018). Soil fauna biodiversity response to urbanization maybe largely a tradeoff between the negative and positive effects of urbanization.…”
Section: Effects Of Urbanization On Soil Fauna Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanization could be harmful to organism as it induced direct habit loss, soil pollution, and strong disturbance (McKinney, 2006;Knop, 2016;Sanchez-Bayo and Wyckhuys, 2019). In contrast, urban habitats provide many resources for soil fauna, such as water from irrigation, food from garbage, and refuge sites in gardens and under paving stones (Jones and Leather, 2012;Hornung et al, 2018;Szlavecz et al, 2018). Soil fauna biodiversity response to urbanization maybe largely a tradeoff between the negative and positive effects of urbanization.…”
Section: Effects Of Urbanization On Soil Fauna Biodiversitymentioning
confidence: 99%
“…In contrast, the effects of urbanization on soil fauna biodiversity are far from a conclusion. There are some studies suggesting that soil fauna biodiversity is higher in less disturbed ecosystems under an urbanization context (Fiera, 2009;Szlavecz et al, 2018;Liu et al, 2019), while some studies find contradictory results (Sterzynska et al, 2018;Joimel et al, 2019). For example, by summarizing 758 studies, Joimel et al (2017) concluded that there are higher soil fauna biodiversity in downtown and industrial areas.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, animals are mobile and their resting locations are not necessarily their feeding locations. To make things even more complex, isopods also discriminate food sources due to different plant species, plant defences (e.g., tannins) and state of microbial decay (Hassall and Rushton 1984; Gunnarsson 1987; Szlávecz and Maiorana 1990) and can probably also differentiate certain contaminants (Loureiro et al 2005; Zidar et al 2012; Žižek and Zidar 2013), including metals (Zidar et al 2005).…”
Section: Isopods In Field Studies and Biomonitoringmentioning
confidence: 99%
“…The capacity of isopods to switch between feeding on dead and green living tissues, i.e., herbivorous feeding, in the field has been demonstrated for several decades. Different isopod species have been observed feeding on green living tissues of several plants even if they have another food source as a choice (Paris and Sikora 1965, Byers et al 1983, Szlávecz and Maiorana 1990, Hopkin 1991, Benetti et al 2002; Morisawa et al 2002; Paoletti et al 2008; Farmer and Dubugnon 2009; Tierranegra-Garcia et al 2010, Faberi et al 2011, Miller 2011, Johnson et al 2012, Faberi et al 2014, 2017). In addition, more recently isopods have been reported to exhibit granivory, i.e., feeding on seeds of weeds and crop plants, of some typical plants in agroecosystems (Saska 2008; Koprdová et al 2012, Salvio et al 2012).…”
Section: Terrestrial Isopods and Food Sources In Agricultural Systemsmentioning
confidence: 99%
“…The preference for or selection of green tissues over decayed leaf litter can be related to the higher N content of green tissues (Szlávecz and Maiorana 1990), or the level or lack of chemical anti-herbivore defense compounds on living plants, e.g. the jasmonate signal pathway (Farmer and Dubugnon 2009) and phenolics (Wood et al 2012).…”
Section: Terrestrial Isopods and Food Sources In Agricultural Systemsmentioning
confidence: 99%